New chameleon Hashing of secure and privacy-preserving vehicular communications - Jian-hong ZHANG; Wei-na ZHEN; Jian-cheng ZOU (Tongxin xuebao)
Many services and applications in vehicular ad-hoc networks (VANET) require preserving and secure data communications.To improve driving safety and comfort,the traffic-related status information will be broadcasted regularly and shared among drivers.Without the security and privacy guarantee,attackers could track their interested vehicles by collecting and analyzing their traffic messages.Hence,anonymous message authentication is an essential requirement of VANET.On the other hand,when a vehicle is involved in a dispute event of warning message,the certificate authority should be able to recover the real identity of this vehicle.To deal with this issue,Guo,et al proposed a new privacy-preserving authentication protocol with authority traceability using elliptic curve based chameleon Hashing.Although this scheme has vehicle identification traceability and high computational efficiency than the previous plan,but analysis shows that the scheme does not meet the anonymity.The security of Guo's scheme is analyzed and improvement is made based on Guo’s protocol.